Novel performance modelling in small and medium-sized enterprises in the pistachio industry - Sorooshian, Shahryar; Zulkifli, Norzima; Ismail, Mohd Yusof; Mohd Yusuff, Rosnah (Academic Journals, 2011)
Among middle east non-oil paramount issues one can refer to pistachio production and its processing industry; Base on this fact, this study attempted to identify the major influences in enhancing success of Middle-East small and medium pistachio processing enterprises, according to their entrepreneur's strategic perception (ESP) and their entrepreneur's background (EB). This research tries to fill the gap of management science empirical researches in small and medium industries, especially pistachio industry. Four concepts of EB, ESP, Entrepreneur's strategy-making activities (ESMA) and performance of small and medium pistachio industry (SMPI) build the prepared empirical model. Modeling and analysis of data performed by using AMOS software, this structural equation model indicated there was a strong association between EB, ESP and Middle East SMPI performance. The model reviewed both direct and indirect effects of the defined variables of the concepts.